Subsidiary Perspective of Coordination Mechanisms on Localization Decisions, Working Environment, Marketing Engagement and New Product Performance - Firmanzah, Firmanzah (Makara Human Behavior Studies in Asia, 2009)
New product launching (NPL) to the local market by subsidiary managers is a strategic activity, which requires organizational supports from MNC global network. The NPL activity is marked by high level of uncertainty, risk, and market failure. Thus, a headquarter needs to integrate the subsidiary NPL into the global strategy. At the same time, subsidiary managers need to have a certain level of autonomy to ensure that the launching program is adapted to the local specificities. These two pressures have forced the subsidiary managers to take up the roles of ‘boundary spanners’. Good working environment between subsidiaries’ managers and headquarter is believed to be the determinant factor for the new product performance. However, good working environment between headquarter and subsidiary is not automatically conditioned. The types of coordination developed by the headquarter influence the subsidiary managers and the headquarter working environment, and hence determine the new product success. This research emphasizes that negotiation coordination is more suitable than the hierarchical coordination when building good working environment during NPL process, determines the commercial performance of new products.